2021
DOI: 10.1055/s-0041-1736174
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Depression and Sexual Function: Are Pregnant Women Affected More Adversely?

Abstract: Objective To investigate depression and sexual function among pregnant and non-pregnant women throughout the COVID-19 pandemic. Methods A total of 188 women, 96 pregnant and 92 non-pregnant were included. The Beck Depression Inventory (BDI) and the Arizona Sexual Experience Scale (ASEX) were applied to the participants after obtaining sociodemographic data. Results The depression scores of pregnant and non-pregnant women were similar (p = 0.846). We found that the depression scores were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
1
0
2
Order By: Relevance
“…While, in the few studies conducted to assess the Italian prevalence of perinatal depression, a highly variable prevalence was observed ranging from 1.6 to 26.6%, even though all of these studies were carried out before the COVID-19 pandemic indeed ( 42 , 56 58 , 64 ). Our findings are in line with previous published (both international and Italian) studies carried out during the COVID-19 pandemic which reported significantly higher depression rates in pregnant women than studies conducted before the pandemic, with a prevalence ranging from 30 to 43% ( 16 , 18 , 29 , 31 , 53 , 65 71 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While, in the few studies conducted to assess the Italian prevalence of perinatal depression, a highly variable prevalence was observed ranging from 1.6 to 26.6%, even though all of these studies were carried out before the COVID-19 pandemic indeed ( 42 , 56 58 , 64 ). Our findings are in line with previous published (both international and Italian) studies carried out during the COVID-19 pandemic which reported significantly higher depression rates in pregnant women than studies conducted before the pandemic, with a prevalence ranging from 30 to 43% ( 16 , 18 , 29 , 31 , 53 , 65 71 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, within this framework, experiencing stressful and subjectively perceived traumatic events, during the perinatal period, may predispose women to the onset of de novo psychopathological manifestations, also in not predisposed pregnant and puerperal women ( 26 ). Therefore, one could argue that the COVID-19 pandemic and related restrictive measurements may have more likely represented a stressful and cumulative traumatic variable which might have modified the psychopathological trajectory in pregnancy and postpartum period, as already reported in the general population ( 27 , 28 ) and in samples constituted by pregnant and postpartum women ( 18 , 29 31 ). In fact, the gradual shaping in health care access and services due to the lockdown and restrictive regulations imposed by governments, including limitations in the access to gynecological, obstetrician and perinatal care and the restricted (or interrupted) possibility for partner and/or family member(s) of pregnant and puerperal women to assist them during pregnancy follow-ups, the delivery and postpartum period, significantly determined a psychological distress, an increased uncertainty and indeed fueled feelings of fears, anxiety and worries among pregnant and postpartum women ( 32 34 ).…”
Section: Introductionmentioning
confidence: 89%
“…The female sexual function index (FSFI) was used in 21 studies to evaluate women's sexual performance. However, one study used the Arizona Sexual Experiences Scale (ASEX) (34). Table 2 shows the specification of the studies that comprised the current systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Sobre o estado psicológico, a pandemia do novo coronavírus teve impacto significativo para o aumento da prevalência de depressão em gestantes, destacando preocupações, que somadas a variação hormonal experimentada por elas, podem resultar em riscos para a continuidade da gravidez (Castro, et al, 2020). No trabalho estabelecido por Denizli et al (2021), 42,7% das gestantes (n=41) apresentaram sintomas leves de depressão ao longo da pandemia, enquanto 21% (n=20) apresentaram sintomas de depressão moderadamente graves. No período gestacional, as alterações fisiológicas e hormonais são comuns e esperadas, o aumento progressivo de concentrações de hormônios esteroides, como estrogênios e progesterona geram mudanças em todo o corpo da gestante, gerando angústias, medos, preocupações, dúvidas e ademais sentimentos.…”
Section: Títulounclassified